Emergency nurse triage in the hospital information management system: A quality improvement study. (November 2021) - Çetin, Songül Bişkin; Cebeci, Fatma; Eray, Oktay; Coşkun, Mustafa; Gözkaya, Meral
Highlights: This study describes how the accuracy and duration of the nurse triage decision is integrated into the hospital information management system (HIMS) and shares an example of the outcome. It points out that the accuracy and duration of nurse triage can be evaluated based on HIMS as an innovation. HIMS-based evaluation; makes nurse triage accuracy and time no longer paper-based, but objective, continuously measurable, auditable and evaluable. offers nurses the ability to review triage decisions, manage performance evaluation and obtain big data. Abstract: Background: Assessment of nurse triage decision accuracy and triage times is currently carried out through paper-based methods. This quality improvement study aims to develop a method that can assess the accuracy and duration of nurse triage decisions based on a computerized system and to share an example of the application of this method. Methods: This is a descriptive quality improvement study. The study was carried out in two stages between March and May 2019. The functionality of the developed method was examined using 3835 patients' triage data, which were obtained between June 1 and 14, 2019. Results: With this study, the determination of the accuracy and duration of nurse triage decisions was accomplished with a computerized process based on real patient outputs, and the accuracy and duration of these decisions were continuously measured, monitored, and assessed, which is different from paper-based methods. The functionality of the method was evaluated with data from 3835 real patients. The triage decision accuracy rate was 64.4%, and the average duration of triage was 81.3s. Positive feedback on the method was received from all triage nurses. Conclusion: The study result outputs can be integrated into quality processes and can be used internationally as performance assessment criteria and quality indicators for triage nursing.